Ductile failure analysis of API steel pipe using strain based failure criteria - Siti Firdaus, Md Salleh (2013)
This project was performed to propose ductile failure criteria as a function of the stress triaxiality for the API X42 steel pipes. The objective of this project is to determine the burst pressure of modeled pipe using strain based failure criteria. In this project, uniaxial tension test was performed using three types of specimen. The specimen extracted from API X42 5L steel pipe. The steel pipe was machined to desired dimension and obeys the international standard of ASTM-E8 specimen. Three type of specimen which is smooth, notch radius 1.5 mm, 3 mm and 6 mm prepared and undergoes uniaxial tension test. The engineering stress-stress data retrieved from the test converted to the true stress-strain curve. The true stress-strain data become as an input data to the simulation analysis. Initial and final diameter of specimen was taken to calculate the strain fracture of the pipe. Stress modified critical strain criteria were proposed by using the strain fracture. The findings of the main parameter which is burst pressure predictions precede by using FEA software. Finite Element analysis was performed by using MSC Patran/Marc 2008r1 software. In MSC Patran, the API X 42 steel pipes was modeled. Burst pressure predicted compared to the available industrial pipe design assessment in order to validate the obtained results.